Preparation method of cellulose-based long afterglow material

By dissolving cellulose in ionic liquid and replacing the long afterglow compound containing halogen, cellulose-based long afterglow material is prepared, solving the problem of complex preparation process and difficult to regulate the afterglow effect in the prior art, and realizing the material Efficient, controllable and excellent afterglow effect.

CN119462972APending Publication Date: 2025-02-18HUNAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411403130.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing preparation methods for cellulose-based long afterglow materials have problems such as uneven dispersion, difficulty in regulating the afterglow effect, and need to add additional catalysts, and physical doping methods have the disadvantages of difficult control of doping concentration.

Method used

Cellulose-based long afterglow material is prepared by dissolving cellulose in an ionic liquid and undergoing substitution reaction with halogen-containing long afterglow compound, combined with the use of anti-solvent. This method requires no additional catalyst, the steps are simple, controllable, and the afterglow effect is adjustable.

Benefits of technology

The efficient preparation of cellulose-based long afterglow materials is achieved. The afterglow effect of the material can be controlled by adjusting the ratio of cellulose and long afterglow groups. The process is gentle and easy to scale, and has good industrial promotion prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119462972A_ABST
    Figure CN119462972A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a cellulose-based long afterglow material. The preparation method comprises the following steps: S1, preparing an ionic liquid capable of dissolving cellulose; s2, adding cellulose into the ionic liquid to prepare a cellulose solution; s3, dissolving a halogen-containing long afterglow compound with an organic solvent, adding the dissolved halogen-containing long afterglow compound into the cellulose solution, and carrying out substitution reaction to obtain a solution containing a cellulose-based long afterglow material; and S4, adding an anti-solvent into the solution prepared in S3 to obtain the cellulose-based long afterglow material. The construction strategy of the cellulose-based long afterglow material is novel and controllable, the construction strategy is classical nucleophilic substitution reaction, compared with the prior art, the afterglow effect can be regulated and controlled, organic alkali left in the reaction in the ionic solution can be directly used as a catalyst of the substitution reaction, the preparation steps are simple, the reaction conditions are mild, and the method is suitable for industrial production. The preparation process is easy to scale, economical and efficient, and has a good industrial popularization prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of functional materials, and more specifically, relates to a method for preparing a cellulose-based long afterglow material. Background Art

[0002] The widespread existence of counterfeit and shoddy products has posed a serious threat to people's health, life and property. The research on anti-counterfeiting materials has gradually become the focus of people's attention. Among them, polymer-based anti-counterfeiting materials have good applications in the field of anti-counterfeiting because of their good processing properties and excellent intelligent recognition performance, for example, Chinese invention patent CN109651416A. However, most of the fluorescent anti-counterfeiting materials currently available use petroleum-based non-degradable polymer materials as matrix materials, which have the disadvantages of being non-degradable and polluting the environment. Nowadays, many bio-based polymer long afterglow materials have been applied to anti-counterfeiting work. For example, Chinese invention patent CN115819939A discloses a biodegradable polylactic acid film with anti-counterfeiting function and a preparation method thereof. However, physical doping has the disadvantage that the doping concentration is difficult to control and it is difficult to present a good afterglow effect by changing its concentration. Therefore, the development of bio-based long afterglow materials with controllable, excellent afterglow effect and stable performance has become a development trend in this field.

[0003] Cellulose is an abundant renewable natural polymer. The presence of a large number of -OH functional groups on its chain segments provides many possibilities for the access of various functional groups and long-lasting groups. It also has unique mechanical and optical properties and can be considered as an ideal carrier for fluorescent groups. There are three main methods for preparing cellulose-based long afterglow materials. The first method is through physical doping, that is, through the interaction of holes or electrons of impurity atoms with holes or electrons in cellulose to form new energy levels. Usually, a substance with a fluorescent group is directly added to a cellulose solid powder such as microcrystalline cellulose (MCC) to interact, thereby changing the fluorescence properties of cellulose to make it a long afterglow material. For example, invention patent CN108059953A discloses a method for preparing a long afterglow luminescent flexible cellulose material, but the physical doping method has problems such as uneven dispersion, and the afterglow effect is difficult to control; the second method is to directly use cellulose as a raw material to prepare a long afterglow material, such as invention patent CN113621262A discloses a polysaccharide long afterglow phosphorescent material. This scheme selects raw materials containing various polysaccharides, and then air-drying, heating or vacuum drying to evaporate the water therein to obtain the material, but this type of method is limited by the addition of additional functional reagents to meet practical applications, and has certain limitations. The third method is to prepare cellulose-based long afterglow materials by chemically integrating cellulose with long afterglow groups. The principle of this method is to utilize the -OH on the cellulose chain segment to undergo a substitution reaction with the long afterglow group, so that the long afterglow group is immobilized on the cellulose, so that the cellulose can be used as a long afterglow material (Nat Commun, 2022, 13, 1117). Compared with methods 1 and 2, this method retains the good processability, mechanical properties and stability of the cellulose (or cellulose derivative) matrix, but it has many reaction steps and requires the addition of additional catalysts. The method of preparing cellulose-based long afterglow materials in situ and in one step by nucleophilic substitution reaction has not been disclosed, so it is urgent to develop a preparation method with simple and controllable preparation steps, no need to add additional catalysts, and adjustable afterglow effect. Summary of the invention

[0004] To solve the above problem, the present invention provides a method for preparing a cellulose-based long afterglow material, which has simple and convenient steps, controllable synthesis process and adjustable afterglow effect.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a cellulose-based long afterglow material comprises the following steps:

[0007] S1. preparing an ionic liquid capable of dissolving cellulose;

[0008] S2. adding cellulose to the ionic liquid to obtain a cellulose solution;

[0009] S3. After dissolving the halogen-containing long afterglow compound in an organic solvent, the cellulose solution is added to cause a substitution reaction to obtain a solution containing a cellulose-based long afterglow material;

[0010] S4. Adding an antisolvent to the solution prepared in S3 to obtain a cellulose-based long afterglow material;

[0011] Furthermore, the ion solution is prepared from an organic acid and an organic base, and the molar ratio of the organic acid to the organic base is 1:1-3.

[0012] Furthermore, the organic acid is one or more of acetic acid, citric acid, succinic acid, levulinic acid, malonic acid, and glutaric acid; the organic base is one or more of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), tetramethylguanidine (TMG), 1,5-diazabicyclo[4.3.0]-5-nonene (DBN), 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD), and triethylamine.

[0013] Furthermore, the cellulose-based long afterglow material has the following structural characteristics:

[0014]

[0015] Wherein: R is independently selected from H or one or more of the following long afterglow groups, and at least one R is a long afterglow group,

[0016]

[0017] Furthermore, in the step S2, the concentration of cellulose in the cellulose solution is 0.5 wt% to 10 wt%, and the process temperature is maintained at 20 to 120°C.

[0018] Furthermore, the organic solvent is one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone, and N,N-dimethylimidazolidinone.

[0019] Further, the halogen-containing long afterglow compound includes one or more of the following compounds: 3-bromophenanthrene, 2-bromophenanthrene, 4-bromopyrene, 4-bromobiphenyl, 1-bromonaphthalene, 4-bromocarbazole, 9-bromoanthracene, 2-bromotriphenylene, and its structural characteristics are as follows:

[0020]

[0021] Furthermore, in the step S3, the molar ratio of cellulose to the halogen-containing long afterglow compound is 1:0.5-10; the reaction time is 1-48 hours; and the reaction temperature is 30-130°C.

[0022] Furthermore, the anti-solvent in step S4 is one or more of ethyl acetate, tetrahydrofuran, anhydrous ethanol, and methanol; and the volume ratio of the anti-solvent to the reaction mixture is 0.5 to 5:1.

[0023] The cellulose-based long afterglow material obtained by the above preparation method is applied to the fields of information encryption, anti-counterfeiting materials and packaging materials.

[0024] Compared with the prior art, the beneficial effects are:

[0025] The present invention utilizes a solvent to dissolve a long afterglow compound containing halogen so that it reacts with a cellulose solution in a homogeneous phase to obtain a cellulose-based long afterglow material. The construction strategy of the cellulose-based long afterglow material is novel and controllable, and the construction strategy is a classic nucleophilic substitution reaction. The afterglow effect of the material can be controlled by changing the ratio of the hydroxyl group to the afterglow group of the cellulose. The present invention uses an ionic liquid prepared by an organic acid and an organic base to dissolve cellulose, and the remaining organic base in the reaction is directly used as a catalyst for the substitution reaction. The preparation steps are simple and convenient, and the bio-based long afterglow material is prepared by a one-pot method. The reaction conditions are mild, the preparation process is easy to scale up, and it is economical and efficient, and has a good prospect for industrial promotion. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 It is the infrared spectra of microcrystalline cellulose MCC and implementation case 1;

[0027] Figure 2 The differential scanning calorimetry test diagram of microcrystalline cellulose MCC and implementation case 1

[0028] Figure 3 Schematic diagram of the afterglow of cellulose-based long afterglow material in implementation case 1. DETAILED DESCRIPTION

[0029] The following is further explained and illustrated in conjunction with the examples, but the specific examples do not limit the present invention in any form. If not specifically stated, the methods and equipment used in the examples are conventional methods and equipment in the art, and the raw materials used are all conventional commercially available raw materials.

[0030] Example 1

[0031] DBU (20.2928 g, 0.136 mol) was added to a two-necked flask. Levulinic acid (13.9344 g, 0.12 mol) was slowly added dropwise to the two-necked flask in an ice-water bath with mechanical stirring. After the addition was completed, stirring was continued at room temperature for a certain period of time. 0.66 g of microcrystalline cellulose (MCC) was weighed and added to the two-necked flask. MCC was dissolved at 60°C to obtain a clear and transparent viscous cellulose solution.

[0032] The two-necked flask containing the cellulose solution prepared above was transferred to a 60°C oil bath, 4-bromobiphenyl (3.79 g, 0.0163 mol) was added to a small flask, 10 ml of N,N-dimethylformamide (DMF) solvent was taken to dissolve 4-bromobiphenyl, and then slowly added dropwise to the two-necked flask, and reacted for 8 hours under vigorous stirring. After stopping the reaction, a transparent solution was obtained, and the volume ratio of the anti-solvent anhydrous ethanol to the reaction mixture was 3:1, and the reaction mixture was added to anhydrous ethanol to regenerate the obtained solid product, which was separated by filtration, washed repeatedly, and freeze-dried to obtain 0.69 g of a solid product.

[0033] The main reaction chemical equation of this embodiment is as follows:

[0034]

[0035] Example 2

[0036] Take DBN (18.216 g, 0.1418 mol) and add it into a two-necked flask. Take levulinic acid (13.9344 g, 0.12 mol) and slowly drop it into the two-necked flask under ice-water bath with mechanical stirring. After the dropwise addition is completed, continue stirring at room temperature for a certain period of time. Weigh 0.59 g of microcrystalline cellulose (MCC) and add it into the two-necked flask. Dissolve MCC at 55°C to obtain a clear and transparent viscous cellulose solution.

[0037] The two-necked flask containing the cellulose solution prepared above was transferred to an oil bath at 80°C, 1-bromonaphthalene (2.25 g, 0.01089 mol) was added to a small flask, 20 ml of DMF solvent was taken to dissolve 1-bromonaphthalene, and then slowly added dropwise to the two-necked flask, and reacted for 8 h under vigorous stirring. After stopping the reaction, a transparent solution was obtained, and the volume ratio of the anti-solvent anhydrous ethanol to the reaction mixture was 2:1, and the reaction mixture was added to anhydrous ethanol to regenerate the obtained solid product, and filtered and separated, and vacuum dried after repeated washing to obtain 0.634 g of solid. The main reaction chemical equation of this embodiment is as follows:

[0038]

[0039] Example 3

[0040] DBU (19.2428 g, 0.1264 mol) was added to a two-necked flask. Acetic acid (7.20 g, 0.12 mol) was slowly added dropwise to the two-necked flask in an ice-water bath with mechanical stirring. After the addition was completed, stirring was continued at room temperature for a certain period of time. 0.52 g of microcrystalline cellulose (MCC) was weighed and added to the two-necked flask. MCC was dissolved at 65°C to obtain a clear and transparent viscous cellulose solution.

[0041] The two-necked flask containing the cellulose solution prepared above was transferred to a 60°C oil bath, 2-bromophenanthrene (1.65 g, 0.0064 mol) was added to a small flask, 20 ml of N, N-dimethylacetamide (DMAC) solvent was taken to dissolve 2-bromophenanthrene, and then slowly added dropwise to the two-necked flask, and reacted for 6 h under vigorous stirring. After stopping the reaction, a transparent solution was obtained, and the volume ratio of the anti-solvent anhydrous ethanol to the reaction mixture was 4:1, and the reaction mixture was added to anhydrous ethanol to regenerate the obtained solid product, filter and separate, and vacuum dry to obtain a solid product after repeated washing. The main reaction chemical equation of this embodiment is as follows:

[0042]

[0043] Example 4

[0044] DBU (20.2158 g, 0.1328 mol) was added to a two-necked flask. Succinic acid (7.0854 g, 0.06 mol) was slowly added dropwise to the two-necked flask in an ice-water bath with mechanical stirring. After the addition was completed, stirring was continued at room temperature for a certain period of time. 0.50 g of microcrystalline cellulose (MCC) was weighed and added to the two-necked flask. MCC was dissolved at 70°C to obtain a clear and transparent viscous cellulose solution.

[0045] The two-necked flask containing the cellulose solution prepared above was transferred to a 60°C oil bath, 4-bromopyrene (3.60 g, 0.0128 mol) was added to a small flask, 15 ml of N, N-dimethylacetamide DMAC solvent was taken to dissolve 4-bromopyrene, and then slowly added dropwise to the two-necked flask, and reacted for 6 hours under vigorous stirring. After stopping the reaction, a transparent solution was obtained, and the volume ratio of the anti-solvent anhydrous ethanol to the reaction mixture was 4:1, and the reaction mixture was added to anhydrous ethanol to regenerate the obtained solid product, filter and separate, and freeze-dry after repeated washing to obtain a solid product. The main reaction chemical equation of this embodiment is as follows:

[0046]

[0047] Example 5

[0048] Take TMG (13.8212 g, 0.12 mol) and add it into a two-necked flask. Take acetic acid (7.20 g, 0.12 mol) and slowly drop it into the two-necked flask under ice-water bath with mechanical stirring. After the dropwise addition is completed, continue stirring at room temperature for a certain period of time. Weigh 0.43 g of microcrystalline cellulose (MCC) and add it into the two-necked flask. Dissolve MCC at 80°C to obtain a clear and transparent viscous cellulose solution.

[0049] The two-necked flask containing the cellulose solution prepared above was transferred to a 90°C oil bath, 4-bromobiphenyl (1.850 g, 0.0079 mol) was added to a small flask, 10 ml of N, N-dimethylformamide DMF solvent was taken to dissolve 4-bromobiphenyl, and then slowly added dropwise to the two-necked flask, and reacted for 12 hours under vigorous stirring. After stopping the reaction, a transparent solution was obtained, and the volume ratio of the anti-solvent anhydrous ethanol to the reaction mixture was 3:1, and the reaction mixture was added to anhydrous ethanol to regenerate the obtained solid product, filter and separate, and freeze-dry after repeated washing to obtain a solid product. The main reaction chemical equation of this embodiment is as follows:

[0050]

[0051] Example 6

[0052] Take DBN (14.90 g, 0.12 mol) and add it into a two-necked flask. Take acetic acid (7.20 g, 0.12 mol) and slowly drop it into the two-necked flask under ice-water bath with mechanical stirring. After the dropwise addition is completed, continue stirring at room temperature for a certain period of time. Weigh 0.45 g of microcrystalline cellulose (MCC) and add it into the two-necked flask. Dissolve MCC at 75°C to obtain a clear and transparent viscous cellulose solution.

[0053] The two-necked flask containing the cellulose solution prepared above was transferred to a 60°C oil bath, 9-bromoanthracene (3.56 g, 0.0138 mol) was added to a small flask, 10 ml of dimethyl sulfoxide (DMSO) solvent was taken to dissolve 9-bromoanthracene, and then slowly added dropwise to the two-necked flask, and reacted for 9 hours under vigorous stirring. After stopping the reaction, a transparent solution was obtained, and the volume ratio of the anti-solvent anhydrous ethanol to the reaction mixture was 2:1, and the reaction mixture was added to anhydrous ethanol to regenerate the obtained solid product, filter and separate, and freeze-dry after repeated washing to obtain a solid product. The main reaction chemical equation of this embodiment is as follows:

[0054]

[0055] Example 7

[0056] DBU (10.04784 g, 0.066 mol) was added to a two-necked flask. Levulinic acid (6.967 g, 0.066 mol) was slowly added dropwise to the two-necked flask in an ice-water bath with mechanical stirring. After the addition was completed, stirring was continued at room temperature for a certain period of time. 0.35 g of microcrystalline cellulose (MCC) was weighed and added to the two-necked flask. MCC was dissolved at 65°C to obtain a clear and transparent viscous cellulose solution.

[0057] The two-necked flask containing the cellulose solution prepared above was transferred to a 120°C oil bath, 4-bromocarbazole (2.12 g, 0.0086 mol) was added to a small flask, 20 ml of N, N-dimethylacetamide DMAC solvent was taken to dissolve 4-bromocarbazole, and then slowly added dropwise to the two-necked flask, and reacted for 4 hours under vigorous stirring. After stopping the reaction, a transparent solution was obtained, and the volume ratio of anti-solvent methanol to the reaction mixture was 3:1, and the reaction mixture was added to anhydrous ethanol to regenerate the obtained solid product, filter and separate, and vacuum dry to obtain a solid product after repeated washing. The main reaction chemical equation of this embodiment is as follows:

[0058]

[0059] Comparative Example 1

[0060] The preparation method of the cellulose solution is the same as that of Example 1. The difference is that the content of the added 4-bromobiphenyl is 4.73 g (0.0203 mol). The preparation method is the same as that of Example 1.

[0061] Comparative Example 2

[0062] The preparation method of the cellulose solution is the same as that of Example 1. The difference is that the content of added 4-bromobiphenyl is 5.69 g (0.0244 mol). The preparation method is the same as that of Example 1.

[0063] Comparative Example 3

[0064] The preparation method of the cellulose solution is the same as that of Example 3. The difference is that the reaction temperature is 100°C. The preparation method is the same as that of Example 3.

[0065] Comparative Example 4

[0066] The preparation method of the cellulose solution is the same as that of Example 3. The difference is that the reaction temperature is 40°C, and the preparation method is the same as that of Example 3.

[0067] Comparative Example 5

[0068] The preparation method of the cellulose solution is the same as that of Example 5. The difference is that the reaction time is 32 hours, and the preparation method is the same as that of Example 5.

[0069] Comparative Example 6

[0070] The preparation method of the cellulose solution is the same as that of Example 5. The difference is that the reaction temperature is 24h, and the preparation method is the same as that of Example 5.

[0071] For the products obtained from the above implementation cases and their long afterglow capabilities, please see Table 1 below:

[0072] Table 1

[0073]

[0074] It can be seen from the table that the long afterglow material prepared by the reaction of cellulose with a halogen-containing long afterglow compound in this experiment has an excellent afterglow effect, and the afterglow can reach more than ten seconds; as shown by the experimental results of Example 3 and Comparative Examples 3 and 4, the afterglow time will gradually decrease with the increase of the reaction temperature; as shown by the experimental results of Example 5 and Comparative Examples 5 and 6, the afterglow time will gradually decrease with the increase of the reaction time; according to the experimental results of Example 1 and Comparative Examples 1 and 2, when the proportion of long afterglow groups in the material increases, the afterglow time will gradually decrease; the above embodiments and comparative examples verify that the afterglow effect of cellulose-based long afterglow materials is affected by the reaction conditions and the proportion of long afterglow groups. According to the above rules, the length of the afterglow time can be controlled by changing the ratio of hydroxyl groups to afterglow groups of cellulose, and a material with adjustable afterglow effect can be prepared.

[0075] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.

Claims

1. A method for preparing a cellulose-based long afterglow material, characterized in that: The steps include: S1. preparing an ionic liquid capable of dissolving cellulose; S2. adding cellulose to the ionic liquid to obtain a cellulose solution; S3. After dissolving the halogen-containing long afterglow compound in an organic solvent, the cellulose solution is added to cause a substitution reaction to obtain a solution containing a cellulose-based long afterglow material; S4. Add an anti-solvent to the solution prepared in S3 to obtain a cellulose-based long afterglow material.

2. The method for preparing a cellulose-based long afterglow material according to claim 1, characterized in that: The ion solution is prepared from an organic acid and an organic base, and the molar ratio of the organic acid to the organic base is 1:1-3.

3. The method for preparing a cellulose-based long afterglow material according to claim 2, characterized in that: The organic acid is one or more of acetic acid, citric acid, succinic acid, levulinic acid, malonic acid, and glutaric acid; the organic base is one or more of 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU), tetramethylguanidine (TMG), 1,5-diazabicyclo[4.3.0]-5-nonene (DBN), 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD), and triethylamine.

4. The method for preparing a cellulose-based long afterglow material according to claim 1, characterized in that: The cellulose-based long afterglow material has the following structural characteristics: Wherein: R is independently selected from H or one or more of the following long afterglow groups, and at least one R is a long afterglow group, 5. The method for preparing a cellulose-based long afterglow material according to claim 1, characterized in that: In the step S2, the concentration of cellulose in the cellulose solution is 0.5 wt% to 10 wt%, and the process temperature is maintained at 20 to 120°C.

6. The method for preparing a cellulose-based long afterglow material according to claim 1, characterized in that: The organic solvent is one of dimethyl sulfoxide, N,N-dimethylformamide, N,N-dimethylacetamide, N-methylpyrrolidone and N,N-dimethylimidazolidinone.

7. The method for preparing a cellulose-based long afterglow material according to claim 1, characterized in that: The halogen-containing long afterglow compound includes one or more of the following compounds: 3-bromophenanthrene, 2-bromophenanthrene, 4-bromopyrene, 4-bromobiphenyl, 1-bromonaphthalene, 4-bromocarbazole, 9-bromoanthracene, 2-bromotriphenylene, Its structural features are as follows:

8. The method for preparing a cellulose-based long afterglow material according to claim 2, characterized in that: In the step S3, the molar ratio of cellulose to the halogen-containing long afterglow compound is 1:0.5-10; the reaction time is 1-48 hours; and the reaction temperature is 30-130°C.

9. The method for preparing a cellulose-based long afterglow material according to claim 1, characterized in that: The anti-solvent in step S4 is one or more of ethyl acetate, tetrahydrofuran, anhydrous ethanol, and methanol; the volume ratio of the anti-solvent to the reaction mixture is 0.5 to 5:

1.

10. The cellulose-based long afterglow material obtained by the preparation method according to any one of claims 1 to 9 is used in the fields of information encryption, anti-counterfeiting materials and packaging materials.

Citation Information

Patent Citations

  • Long afterglow luminescent flexible nano cellulose material, preparation method and applications thereof

    CN108059953A

  • Three-color fluorescent anti-counterfeit material based on excitation wavelength dependence, preparation method and application thereof

    CN109651416A

  • Polysaccharide long-afterglow material and application thereof

    CN113621262A

  • Biodegradable polylactic acid film with anti-counterfeiting function and preparation method thereof

    CN115819939A